Log based petrophysical analysis of mio-pliocene sandstone reservoir encountered in well Rashidpur 4 of Bengal Basin in Bangladesh - Farhaduzzaman, M; Islam, MA; Abdullah, WH; Dutta, J (Bangladesh Journal of Scientific and Industrial Research, 2016)
Rashidpur is located in the northeastern part of Bangladesh which is surrounded on three sides by India and on a small portion by Myanmar. Gamma-ray, spontaneous potential, density, neutron, resistivity, caliper, temperature and sonic logs are used to analyze petrophysical parameters of the well Rashidpur 4, Bangladesh. Quantitative measurements of different factors such as shale volume, porosity, permeability, water saturation, hydrocarbon saturation and bulk volume of water are carried out using well logs. Petrographic and XRD results based on several core samples are also compared with log-derived parameters. Twenty permeable zones are identified whereby four are hydrocarbon bearing in the studied Mio-Pliocene reservoir sandstones. Measured shale volume ranges from 11% to 38% and porosity is 19% to 28%. However, log-derived porosity is slightly higher than the thin section porosity. Water saturation of the interested zones varies from 14% to 38%, 13% to 39% and 16% to 41% measured from Schlumberger, Fertl and Simandoux formula respectively. Conversely, hydrocarbon saturation of the examined hydrocarbon zones ranges from 62% to 86%, 61% to 83% and 59% to 84% respectively. In the analyzed zones, the permeability values are calculated as 28-305 mD. Good to very good quality hydrocarbon reservoirs are appraised for the studied four zones based on the petrophysical parameters, petrographic observation and XRD analysis. Among these, Zone 4 is the best quality reservoir for hydrocarbon. Bangladesh J. Sci. Ind. Res. 51(1), 23-34, 2016